Active suspension for trucks incorporating frame flexibility effects. (4th August 2014) - Ibrahim, I.M.; Crolla, D.A.; Barton, D.C.
The aim of the paper is to investigate the design of active suspensions aimed at improving of the ride vibration behaviour of trucks and incorporating the effects of the flexible frame in the dynamic behaviour. The work is a theoretical study and deals with improvements of the ride comfort, structural acceleration, suspension working spaces and dynamic tyre loads. The road surface profile is considered to be a continuous, random process and is modelled as a filtered white noise excitation. The time delay between the excitation inputs of the vehicle axles is included and modelled using the Pade approximation technique. The FEM (finite element method) and the modal superposition theory have been used to calculate the modal properties of the frame structure. The Lagrangian approach has been applied to obtain the energy equations of the vehicle system motions which result from the well known rigid body modes and from the modal parameters of the frame structure flexibility. Linear stochastic optimal control theory has been used to obtain the optimal active suspension for the truck system based on the full state controller strategy. The performance of the passive system is compared with the performance of the optimal actively controlled systems for two cases, one in which control law accounts for the "preview" effect that the input at the rear is a delayed version of that at the front (referred to as correlated) and one in which the control law does not (uncorrelated). The results show that the modelling technique is a useful design aid for studying the dynamics and control of complex vehicle structures. It is shown that active suspension controllers offer significant improvements over passive systems in acceleration levels, suspension workspace and dynamic tyre load.